2006
DOI: 10.1007/s00436-006-0237-5
|View full text |Cite
|
Sign up to set email alerts
|

A relevant enzyme in granulomatous reaction, active matrix metalloproteinase-9, found in bovine Echinococcus granulosus hydatid cyst wall and fluid

Abstract: In addition to the ability of matrix metalloproteinases (MMP) to degrade components of the extracellular matrix and their involvement in pathology-related processes of tissue remodeling, they were recently reported to enhance inflammation by activation of proinflammatory cytokines, or their release from the cell surface. In the work reported here, proteolytic activity previously found for hydatid cysts was further characterized as MMP-9. Active host MMP-9 was found in walls and fluids of bovine hydatid cysts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
3
16
1
3
Order By: Relevance
“…Host immunoglobulins and albumin [48, 49, 51, 52], activators and inhibitors of the complement cascade [50, 53] and, recently, host-derived active matrix metalloproteinase 9, which was assumed to play a role in the periparasitic granulomatous reactions [54], were found in Echinococcus sp. hydatid fluid or bound to the cyst wall.…”
Section: The Cross-talk Between E Multilocularis Larvae and Theirmentioning
confidence: 99%
“…Host immunoglobulins and albumin [48, 49, 51, 52], activators and inhibitors of the complement cascade [50, 53] and, recently, host-derived active matrix metalloproteinase 9, which was assumed to play a role in the periparasitic granulomatous reactions [54], were found in Echinococcus sp. hydatid fluid or bound to the cyst wall.…”
Section: The Cross-talk Between E Multilocularis Larvae and Theirmentioning
confidence: 99%
“…in endothelial cells, lymphocytes and macrophages. Furthermore, the expression of certain MMPs and plasminogen activators is also increased in liver cells during liver regeneration [19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 [19,30]. Discriminant analysis revealed that the association of two or more markers significantly increased their efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Effector mechanisms include neutrophils and macrophage activation, nitric oxide (NO), eosinophil cationic protein, complement, and antibodies (Virginio et al 2007;Amri et al 2007;Ferreira et al 2000a;Heath et al 1994;Jenkins et al 1990;Ramos et al 2006;Ferragut and Nieto 1996;Severi et al 1997;Zhang et al 2003b;Riley et al 1986;Dempster et al 1992). Around live intact cysts there is a remarkably scarce inflammatory reaction, as opposed to regressive cysts (Breijo et al 2008;Coltorti and Varela-Diaz 1974;Marco et al 2006;Sakamoto and Cabrera 2003). Although it is not clear whether the inflammatory reaction is the cause of cyst inactivation or the consequence of hydatid cyst fluid (HCF) spillage from spontaneously damaged cysts, some evidence exists that cysts can be damaged by an early pericystic inflammatory reaction (Fotiadis et al 1999).…”
Section: Immune Response To E Granulosusmentioning
confidence: 98%
“…Each viable protoscolex (PSC) may develop into an adult worm if ingested by a definitive host or into a new cyst if disseminated in tissues of an intermediate host as the consequence of cyst rupture (secondary hydatidosis). Around intact cysts there is a remarkably scarce inflammatory reaction (Breijo et al 2008;Coltorti and Varela-Diaz 1974;Marco et al 2006;Sakamoto and Cabrera 2003).…”
Section: The Hydatid Cyst and Its Natural Historymentioning
confidence: 99%